2020
DOI: 10.3847/1538-4357/ab6a9b
|View full text |Cite
|
Sign up to set email alerts
|

Deflating Super-puffs: Impact of Photochemical Hazes on the Observed Mass–Radius Relationship of Low-mass Planets

Abstract: The observed mass-radius relationship of low-mass planets informs our understanding of their composition and evolution. Recent discoveries of low mass, large radii objects ("super-puffs") have challenged theories of planet formation and atmospheric loss, as their high inferred gas masses make them vulnerable to runaway accretion and hydrodynamic escape. Here we propose that high altitude photochemical hazes could enhance the observed radii of low-mass planets and explain the nature of super-puffs. We construct… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

14
82
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 67 publications
(96 citation statements)
references
References 150 publications
(207 reference statements)
14
82
0
Order By: Relevance
“…Rather than fitting a parameterized cloud model, we instead investigate whether microphysical models of photochemical hazes can match our observations. Although these same microphysical models can also be used to study condensate cloud formation, Gao & Zhang (2020) found that photochemical hazes dominate the scattering opacity for planets with temperatures similar to that of Kepler-79d.…”
Section: Fitting the Wfc3 Spectrum And Kepler Wlc Depthmentioning
confidence: 99%
See 3 more Smart Citations
“…Rather than fitting a parameterized cloud model, we instead investigate whether microphysical models of photochemical hazes can match our observations. Although these same microphysical models can also be used to study condensate cloud formation, Gao & Zhang (2020) found that photochemical hazes dominate the scattering opacity for planets with temperatures similar to that of Kepler-79d.…”
Section: Fitting the Wfc3 Spectrum And Kepler Wlc Depthmentioning
confidence: 99%
“…The relatively low densities of super-puffs also make them highly vulnerable to atmospheric mass loss, either due to photoevaporation or Parker wind-like outflow (Lopez & Fortney 2014;Owen & Wu 2016;Cubillos et al 2017;Wang & Dai 2019;Gao & Zhang 2020). The latter mechanism is important for super-puffs because their low gravities result in non-negligible densities at the Bondi radius.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…boundary. Second, it is possible that high-altitude aerosols or hazes could be affecting the radius of HD332231b(e.g., Lammer et al 2016;Gao & Zhang 2020). This caveat could be tested through atmospheric characterization.…”
Section: A Planet On the Border Between Neptunian And Jovian Classesmentioning
confidence: 99%